Structure-based pharmacophore modeling, high-throughput screening, and molecular dynamics identify a novel DrugBank-derived HIV-1 protease inhibitor - Ali Sultan Khazaal Nazal; Amjed Majid Rashid Alrashedi; Lamia Abdultef Risan Al-Iessa; Mustafa Abdulkadhim Hussein Ali Rabeea (PLoS ONE, 2026)
HIV-1 protease (PR) is required for viral maturation and is a major antiretroviral target. In this study, a structure-based pharmacophore modeling, drug repurposing, docking, and molecular dynamics (MD) was applied to discover new PR inhibitors. A pharmacophore model was generated from the HIV-1 PR–3TL complex (PDB 3KFP) and used to screen the DrugBank library and hit identification. The identified hit and reference 3TL were docked into PR, and each complex was simulated for 100 ns. Key metrics, including binding energy, RMSD, RMSF, SASA, hydrogen bonds, salt bridges, PCA were analyzed and compared. Through the screening, one hit, HONH-BENZYLMALONYL-L-ALANYLGLYCINE-P-NITROANILIDE (DrugBank Accession Number: DB07434) (BAN), was identified. Docking predicted BAN’s binding energy (–7.51 kcal/mol) slightly better than 3TL (–7.05 kcal/mol). MD showed BAN established a dense H-bond network, including Asp25, and a highly favorable total interaction energy (–69 kJ/mol). However, BAN binding significantly increased protease flexibility. BAN-bound PR had higher backbone RMSD (0.34 nm) and RMSF (0.215 nm) than 3TL-bound (0.22 nm, 0.121 nm), and disrupted salt bridges that remained stable with 3TL. PCA revealed BAN-bound PR sampled a larger conformational space. SASA changes were minor in all systems. BAN binds HIV-1 PR with affinity comparable to 3TL but via a distinct mechanism, stronger polar interactions accompanied by greater protein flexibility. These results, supported by recent literature, suggest BAN as a novel scaffold for PR inhibition. Experimental validation of BAN’s inhibitory activity is warranted.